Neuropsychiatric Symptoms Assessment: Cross-cultural Adaptation and Validation of the Portuguese Abe's BPSD Score (ABS). Issue 3 (27th May 2022) - Ferreira, Ana Rita; Sá, Andreia; Dias, Claudia Camila; Simões, Mário R.; Abe, Koji; Fernandes, Lia
ABSTRACT: Objectives: This study aims to report on the development and psychometric properties of the Portuguese-language Abe's BPSD score (ABS) to screen for neuropsychiatric symptoms (NPS). Methods: ISPOR and COSMIN recommendations were followed to translate and culturally adapt the ABS. A validation study was conducted to assess the psychometric properties of the newly-translated instrument. Outpatients attending a psychogeriatric consultation were included by consecutive referrals and were assessed with the ABS, the Neuropsychiatric Inventory (NPI) and NPI Caregiver Distress scale (NPI-D), and the Mini-Mental State Examination (MMSE). The ABS reliability (internal consistency, item-total correlations, inter-rater and test-retest reliability), validity (concurrent and convergent), feasibility and diagnostic accuracy were examined. Results: Overall, 107 participants were included. The ABS Cronbach alpha was 0.672, and item-total correlations ranged from −0.056 to 0.546. Strong inter-rater (ICC 0.997; 95%CI: 0.995–0.999) and test-retest reliability (ICC 0.976; 95%CI: 0.958–0.986) were found. Concurrent validity with NPI was high (rs  = 0.847, p < .001), and correlations with MMSE and NPI-D were also significant. An exploratory threshold score ≥2 is proposed to identify clinically relevant NPS. Conclusions: Data provide satisfactory proof of ABS psychometric characteristics. Nevertheless, some items exhibited less optimal properties. Clinical Implications: The newly-translated instrument proved to be relevant, valid and easy to use in a real geriatric clinical setting.